ATRT-24. CDK7 Inhibition in AT/RT. (3rd June 2022) - Morin, Andrew; Wodetzki, Darya; Veo, Bethany; Pierce, Angela; Zahedi, Shadi; Crespo, Michele; Venkataraman, Sujatha; Vibhakar, Rajeev; Mulcahy-Levy, Jean
Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) are CNS tumors with a 5-year survival of ~35%. AT/RT is characterized by loss-of-function mutations in the SMARCB1 component of the SWI/SNF (SWItch/Sucrose Non-Fermentable) complex. Based on preliminary CRISPR-Cas9 gene essentiality screen results identifying AT/RT vulnerabilities, we hypothesized that interaction between CDK7 and the SWI/SNF complex via SMARCB1 provides a potential target to improve clinical survival of patients. CDK7 expression was identified by microarray in AT/RT, medulloblastoma, glioblastoma and normal brain. Established cell lines (BT12, BT16, CHLA06), patient derived lines (MAF-737, MAF-1298, MAF-1337), normal human astrocytes (NHA) and NIH3T3 mouse embryonic fibroblast cells were utilized for in vitro response to CDK7 inhibition. Murine cerebellar xenografts of MAF-737 were utilized to evaluate genetic and pharmacologic response to CDK7 inhibition. The NCI Approved Oncology Drugs (AOD-9) Panel was evaluated with an IC25 dose of CDK7 inhibitor THZ2 to identify potential synergistic combinations. CDK7 is up-regulated in AT/RT compared to other brain tumors or normal brain. In vitro, AT/RT cells are highly susceptible to CDK7 pharmacologic inhibition with nM IC50 levels. AT/RT cells with shRNA against CDK7 implanted in vivo show significantly reduced growth. Evaluation of in vivo tumors treated with THZ2 demonstrate decreased Ki-67 and reduced pRBP1 demonstrating effective inhibition of the target as well as a decrease in cell proliferation. Combination therapy of THZ2 with the AOD-9 Panel found significant synergy with antimetabolite therapies, specifically pemetrexed, pralatrexate, and methotrexate. There was no synergy with other standard chemotherapy. Our findings demonstrate that CDK7 is highly expressed in AT/RT and necessary for proliferation of AT/RT cells, suggesting it as a potential therapeutic target. Antimetabolites, which are currently used in several AT/RT protocols, synergized with CDK7 inhibition offers a potential future combination therapy for patients.